Bridging Between Japan-Originated Inorganic Chemistry Theories and the Latest DFT Calculations - Takashiro Akitsu (Molecules)
There are two concepts that were discovered by Japanese researchers that appear in most inorganic chemistry textbooks: the spectrochemical series [...]